A heavy metal adsorbent for acidic antimony mine wastewater and its preparation method and application
By preparing sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent, the problems of large consumption, high cost and pH sensitivity in the wastewater treatment of small and medium-sized antimony ore are solved, and high-value resource treatment is provided for electrolytic manganese slag, achieving efficient removal of lead and antimony heavy metals in acid antimony ore wastewater.
Patent Information
- Application Number
- CN202411783256.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
In the treatment of small and medium-sized antimony ore wastewater, adsorbent consumption is high, cost is high, and applicable to pH sensitivity. A large amount of manganese slag accumulation leads to waste of land resources, which requires harmless resource treatment.
Using materials such as sodium alginate, electrolytic manganese slag and polyacrylamide, a highly efficient selective adsorption gel is prepared by a simple hydrothermal method to remove lead and antimony heavy metals in acid antimony ore wastewater.
This adsorbent overcomes the problems of large consumption, high cost and pH sensitivity of traditional adsorbents, and provides a high-value resource utilization method for electrolytic manganese slag, showing good adsorption performance of lead-antimony heavy metal ions, especially in the range of pH=4~6.
Smart Images

Figure CN119236904B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental heavy metal removal, and specifically relates to an acid antimony mine wastewater heavy metal adsorbent and a preparation method and application thereof. Background Art
[0002] Acidic antimony mine wastewater is a typical mine wastewater. Typical heavy metal ions in antimony mine wastewater include heavy metals such as lead and antimony. Heavy metals such as lead and antimony enter the body of animals, plants and humans and accumulate in the body, causing the death of animals and plants and the risk of teratogenicity and cancer in humans. Due to the low pH and high heavy metal content of acidic antimony mine wastewater, heavy metals in acidic antimony mine wastewater are mostly treated by electrochemical and coagulation methods. However, due to its high energy consumption, small and medium-sized antimony mines cannot afford it. Therefore, most small and medium-sized antimony mine wastewater treatment uses adsorption method, but it faces problems such as large adsorbent consumption, high cost, and pH sensitivity.
[0003] The acid leaching residue produced by electrolytic manganese is called Electrolytic Manganese Residue (EMR). Every ton of manganese metal produced will produce 7-9 tons of electrolytic manganese slag. EMR is a Class II general industrial solid waste. The accumulation of a large amount of manganese slag will cause a waste of land resources. From the chemical composition of electrolytic manganese slag, electrolytic manganese slag is mainly composed of silicon dioxide, aluminum oxide, iron oxide, magnesium oxide, etc. Therefore, it is of great practical significance to utilize electrolytic manganese slag as a resource. Summary of the invention
[0004] The purpose of the present invention is to provide a heavy metal adsorbent for acidic antimony mine wastewater and a preparation method and application thereof, so as to solve the problem mentioned in the background technology that most of the current small and medium-sized antimony mine wastewater treatment adopts the adsorption method, but faces the problems of large adsorbent consumption, high cost, and pH sensitivity, as well as the problem that a large amount of manganese slag accumulation will cause a waste of land resources and requires harmless resource treatment.
[0005] To achieve the above object, the present invention provides a method for preparing a heavy metal adsorbent for acidic antimony mine wastewater, comprising the following steps:
[0006] S1, adding sodium alginate into the aqueous solution, stirring at a constant temperature, to obtain a paste-like uniform sodium alginate aqueous solution;
[0007] S2, adding electrolytic manganese slag to the sodium alginate aqueous solution, stirring and ultrasonically treating to form a uniform first solution;
[0008] S3, preparing an ammonium persulfate (APS) initiator solution, adding it to the first solution to obtain a second solution;
[0009] S4, preparing a sodium hydroxide solution and an acrylic acid (AA) solution, and adding them into the second solution to obtain a third solution;
[0010] S5, preparing an acrylamide (AM) solution, and adding it into the third solution to obtain a fourth solution;
[0011] S6, preparing NN methylenebisacrylamide (MBA) solution, and adding it into the fourth solution to obtain a fifth solution;
[0012] Under the hydroponic condition of 60-65° C., the fifth solution is subjected to a cross-linking reaction. After the cross-linking reaction is completed, the adsorption gel is washed with deionized water until it is neutral and dried to obtain a sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent.
[0013] In a specific embodiment, in step S6, the cross-linking reaction time is 8 to 12 hours.
[0014] In a specific embodiment, in step S1, the sodium alginate is analytically pure; the mass-to-liquid ratio of the sodium alginate aqueous solution is 5g:35-45ml; the stirring temperature is 80-90°C, and the stirring time is 30-40min.
[0015] In a specific embodiment, in step S2, the stirring ultrasonic treatment includes stirring for 15 to 20 minutes at a rotation speed of 30 r / min, and ultrasonicating for 15 to 30 minutes at an ultrasonic power of 200 W; the pretreatment of the electrolytic manganese slag includes: calcining at 400-600°C, crushing and then passing through a 100 mesh sieve to obtain the undersize.
[0016] In a specific embodiment, the mass ratio of sodium alginate to electrolytic manganese slag is 5:2-3; the mass ratio of sodium alginate to ammonium persulfate (APS) initiator is 5:0.1-0.15; the mass ratio of sodium alginate to sodium hydroxide is 5:1-1.5; the mass volume ratio of sodium alginate to acrylic acid (AA) is 5g:3-5ml; the mass ratio of sodium alginate to acrylamide (AM) is 5:0.8-1.2; the mass ratio of sodium alginate to NN methylenebispropylene (MBA) is 5:0.3-0.4.
[0017] In a specific embodiment, in step S3, the temperature when the first solution is added is 75-80°C, and the reaction is carried out for 3-5 minutes after the first solution is added; in step S4, the temperature when the second solution is added is 75-80°C, and the reaction is carried out for 3-5 minutes after the second solution is added; in step S5, the temperature when the third solution is added is 75-80°C, and the reaction is carried out for 3-5 minutes after the third solution is added.
[0018] In a specific implementation, in step S6, the drying temperature is 60-80°C.
[0019] The present invention also provides a heavy metal adsorbent for acidic antimony mine wastewater, which is prepared by the preparation method of the heavy metal adsorbent for acidic antimony mine wastewater as described above.
[0020] The present invention also provides an application of a heavy metal adsorbent for acidic antimony mine wastewater. The heavy metal adsorbent for acidic antimony mine wastewater is the heavy metal adsorbent for acidic antimony mine wastewater as described above, and is applied to remove heavy metals such as lead and antimony in acidic antimony mine wastewater.
[0021] In a specific implementation, the pH of the acidic antimony mine wastewater is first adjusted to 4-6, and the amount of the heavy metal adsorbent for acidic antimony mine wastewater added to each liter of acidic antimony mine wastewater is 0.6-1 g.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses Class II general industrial solid waste electrolytic manganese slag as raw material, adds composite sodium alginate and polyacrylamide, and prepares a highly efficient selective adsorption gel by a simple hydrothermal method. It provides a new material for adsorbing heavy metals such as lead and antimony in acidic antimony mine wastewater, and also provides a new way for high-value resource utilization of electrolytic manganese slag.
[0024] From the chemical composition of electrolytic manganese slag, electrolytic manganese slag is mainly composed of silicon dioxide, aluminum oxide, iron oxide, magnesium oxide, etc., and has clay-like mineral characteristics. Using electrolytic manganese slag alone as a heavy metal adsorbent has the disadvantages of difficulty in recovering particles and low adsorption capacity.
[0025] The high-efficiency selective adsorption gel prepared by the present invention not only overcomes the difficulty of separating and recycling the powder of the general activated electrolytic manganese slag adsorbent, but also overcomes the problems of poor mechanical properties of the sodium alginate-based adsorbent. In addition, the present invention has good adsorption performance for single lead and antimony heavy metal ions, and when two heavy metals exist at the same time, the composite adsorbent has good selective adsorption for trivalent antimony ions. Therefore, the present invention not only provides a new path for the high-value resource utilization of electrolytic manganese slag, but also provides a new material for adsorbing and removing lead and antimony heavy metal ions in acidic antimony mine wastewater.
[0026] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention is further described in detail below. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0028] Figure 1The present invention is a flow chart of a method for preparing a heavy metal adsorbent for acidic antimony mine wastewater.
[0029] Figure 2 is the TG thermogravimetric diagram of the sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent prepared by the present invention; Figure 2 It can be known that the sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent prepared by the present invention has a heat loss of 41% within 600° C., which is mainly the loss mass of the natural polysaccharide sodium alginate and the polyacrylamide formed by polymerization.
[0030] Figure 3 is a SEM image of the sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent prepared by the present invention. Figure 3 It can be seen that the sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent has a porous structure.
[0031] Figure 4 This is the FTIR graph of the sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent prepared by the present invention. Figure 4 It can be seen that the sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent prepared by the present invention has abundant oxygen-containing functional groups, amide groups and silicon-oxygen bonds, which provide a functional group basis for the subsequent adsorption and complexation of lead and antimony heavy metals, indicating that the adsorbent was successfully prepared. DETAILED DESCRIPTION
[0032] The embodiments of the present invention are described in detail below. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] The present invention provides a method for preparing a heavy metal adsorbent for acidic antimony mine wastewater, comprising the following steps:
[0034] S1, adding sodium alginate into the aqueous solution, stirring at a constant temperature, to obtain a paste-like uniform sodium alginate aqueous solution;
[0035] S2, adding electrolytic manganese slag to the sodium alginate aqueous solution, stirring and ultrasonically treating to form a uniform first solution;
[0036] S3, preparing an ammonium persulfate (APS) initiator solution, adding it to the first solution to obtain a second solution;
[0037] S4, preparing a sodium hydroxide solution and an acrylic acid (AA) solution, and adding them into the second solution to obtain a third solution;
[0038] S5, preparing an acrylamide (AM) solution, and adding it into the third solution to obtain a fourth solution;
[0039] S6, preparing NN methylenebisacrylamide (MBA) solution, and adding it into the fourth solution to obtain a fifth solution;
[0040] Under the hydroponic condition of 60-65° C., the fifth solution is subjected to a cross-linking reaction. After the cross-linking reaction is completed, the adsorption gel is washed with deionized water until it is neutral and dried to obtain a sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent.
[0041] When the hydroponic culture temperature is lower than 60℃, it cannot be formed within the appropriate time and it takes a longer time to form an adsorption gel; when the hydroponic culture temperature is higher than 65℃, cross-linking is often unsuccessful and the gel becomes a hard mass lacking in elasticity.
[0042] In step S6, the cross-linking reaction time is 8 to 12 hours.
[0043] In step S1, the sodium alginate is analytical grade; the mass-to-liquid ratio of the sodium alginate aqueous solution is 5 g:35-45 ml; the stirring temperature is 80-90° C., and the stirring time is 30-40 min.
[0044] In the step S2, the stirring ultrasonic treatment includes stirring for 15-20 minutes at a rotation speed of 30 r / min, and ultrasonicating for 15-30 minutes at an ultrasonic power of 200 W; the pretreatment of the electrolytic manganese slag includes: calcining at 400-600° C., crushing and then passing through a 100-mesh sieve to obtain the undersize.
[0045] The mass ratio of sodium alginate to electrolytic manganese slag is 5:2-3; the mass ratio of sodium alginate to ammonium persulfate (APS) initiator is 5:0.1-0.15; the mass ratio of sodium alginate to sodium hydroxide is 5:1-1.5; the mass volume ratio of sodium alginate to acrylic acid (AA) is 5g:3-5ml; the mass ratio of sodium alginate to acrylamide (AM) is 5:0.8-1.2; the mass ratio of sodium alginate to NN methylenebispropylene (MBA) is 5:0.3-0.4.
[0046] In the step S3, the temperature when the first solution is added is 75-80°C, and the reaction takes 3-5 minutes after the first solution is added; in the step S4, the temperature when the second solution is added is 75-80°C, and the reaction takes 3-5 minutes after the second solution is added; in the step S5, the temperature when the third solution is added is 75-80°C, and the reaction takes 3-5 minutes after the third solution is added.
[0047] In step S6, the drying temperature is 60-80°C.
[0048] The present invention also provides a heavy metal adsorbent for acidic antimony mine wastewater, which is prepared by the preparation method of the heavy metal adsorbent for acidic antimony mine wastewater as described above.
[0049] The present invention also provides an application of a heavy metal adsorbent for acidic antimony mine wastewater. The heavy metal adsorbent for acidic antimony mine wastewater is the heavy metal adsorbent for acidic antimony mine wastewater as described above, and is applied to remove heavy metals such as lead and antimony in acidic antimony mine wastewater.
[0050] First, the pH value of the acidic antimony mine wastewater is adjusted to 4-6, and the amount of the heavy metal adsorbent for acidic antimony mine wastewater added to each liter of the acidic antimony mine wastewater is 0.6-1 g.
[0051] Example 1
[0052] A method for preparing a heavy metal adsorbent for acidic antimony mine wastewater comprises the following steps:
[0053] S1. Accurately weigh 5g of sodium alginate into a beaker, add 40ml of deionized water, place on a magnetic stirrer at 90℃, 30r / min and stir for 30min to obtain a uniform sodium alginate aqueous solution.
[0054] S2. Accurately weigh 2 g of electrolytic manganese slag and add it to the uniformly gelatinized sodium alginate solution in step 1. Stir at 30 r / min for 15 min. Place it in an ultrasonic cleaner with an ultrasonic power of 200 W and perform ultrasonic cleaning for 15 min to obtain a uniformly mixed sodium alginate / electrolytic manganese slag solution.
[0055] S3. Accurately weigh 0.1 g of ammonium persulfate (APS) initiator, dissolve it in 2 ml of deionized water, add the sodium alginate / electrolytic manganese slag solution in step 2 at 75°C, and react for 3 minutes.
[0056] S4. Accurately weigh 1g of sodium hydroxide, dissolve it in 10ml of deionized water, measure 4ml of acrylic acid (AA), add it to the solution in step 3 at 75℃, and react for 5min.
[0057] S5. Accurately weigh 1 g of acrylamide (AM), dissolve it in 5 ml of deionized water, add it to the solution in step 4 at 75°C, and react for 5 min.
[0058] S6. Accurately weigh 0.4 g of N-N-methylenebispropylene (MBA), dissolve it in 20 ml of deionized water, add it to the solution in step 5, culture it in water at 65°C, and cross-link it for 8 hours. After the reaction is completed, rinse it with deionized water until it is neutral, and dry it at 60°C to obtain sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent, which is recorded as SA-EMR. 5∶2 .
[0059] Example 2
[0060] A method for preparing a heavy metal adsorbent for acidic antimony mine wastewater comprises the following steps:
[0061] S1. Accurately weigh 5g of sodium alginate into a beaker, add 40ml of deionized water, place on a magnetic stirrer at 90℃, 30r / min and stir for 30min.
[0062] S2. Accurately weigh 2.5 g of electrolytic manganese slag and add it to the uniformly gelatinized sodium alginate solution in step 1. Stir at 30 r / min for 15 min. Place it in an ultrasonic cleaner with an ultrasonic power of 200 W and ultrasonicate for 15 min to obtain a uniformly mixed sodium alginate / electrolytic manganese slag solution.
[0063] S3. Accurately weigh 0.1 g of ammonium persulfate (APS) initiator, dissolve it in 2 ml of deionized water, add the sodium alginate / electrolytic manganese slag solution in step 2 at 75°C, and react for 3 minutes.
[0064] S4. Accurately weigh 1g of sodium hydroxide, dissolve it in 10ml of deionized water, measure 4ml of acrylic acid (AA), add it to the solution in step 3 at 75℃, and react for 5min.
[0065] S5. Accurately weigh 1 g of acrylamide (AM), dissolve it in 5 ml of deionized water, add it to the solution in step 4 at 75°C, and react for 5 min.
[0066] S6. Accurately weigh 0.4 g of N-N-methylenebispropylene (MBA), dissolve it in 20 ml of deionized water, add it to the solution in step 5, culture it in water at 65°C, and cross-link it for 8 hours. After the reaction is completed, rinse it with deionized water until it is neutral, and dry it at 60°C to obtain sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent, which is recorded as SA-EMR. 2∶1 .
[0067] Example 3
[0068] A method for preparing a heavy metal adsorbent for acidic antimony mine wastewater comprises the following steps:
[0069] S1. Accurately weigh 5g of sodium alginate into a beaker, add 40ml of deionized water, place on a magnetic stirrer at 90℃, 30r / min and stir for 30min.
[0070] S2. Accurately weigh 3 g of electrolytic manganese slag and add it to the uniformly gelatinized sodium alginate solution in step 1. Stir at 30 r / min for 15 min. Place it in an ultrasonic cleaner with an ultrasonic power of 200 W and ultrasonicate for 15 min to obtain a uniformly mixed sodium alginate / electrolytic manganese slag solution.
[0071] S3. Accurately weigh 0.1 g of ammonium persulfate (APS) initiator, dissolve it in 2 ml of deionized water, add the sodium alginate / electrolytic manganese slag solution in step 2 at 75°C, and react for 3 minutes.
[0072] S4. Accurately weigh 1g of sodium hydroxide, dissolve it in 10ml of deionized water, measure 4ml of acrylic acid (AA), add it to the solution in step 3 at 75℃, and react for 5min.
[0073] S5. Accurately weigh 1 g of acrylamide (AM), dissolve it in 5 ml of deionized water, add it to the solution in step 4 at 75°C, and react for 5 min.
[0074] S6. Accurately weigh 0.4 g of N-N-methylenebispropylene (MBA), dissolve it in 20 ml of deionized water, add it to the solution in step 5, culture it in water at 65°C, and cross-link it for 8 hours. After the reaction is completed, rinse it with deionized water until it is neutral, and dry it at 60°C to obtain sodium alginate / electrolytic manganese slag / polyacrylamide adsorbent, which is recorded as SA-EMR. 5∶3 .
[0075] About SA-EMR 5∶2 、SA-EMR 2∶1 、SA-EMR 5∶3 The swelling properties of the three adsorbents were tested to obtain SA-EMR 5∶2 The swelling rate of SA-EMR is 473.2%. 2∶1 The swelling rate of SA-EMR is 531.9%. 5∶3 The swelling rate of SA-EMR is 140.3%. 2∶1 The swelling property is the best.
[0076] Choose SA-EMR 2∶1 Conduct effect verification 1.
[0077] (1) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: pH 6, 250 ml, 12.5 mg / L Sb 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Sb in the solution was determined by atomic absorption spectrometry. 3+ The ion concentrations are shown in Table 1.
[0078] Table 1:
[0079]
[0080] (2) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: pH 6, 250 ml, 25 mg / L Sb 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Sb in the solution was determined by atomic absorption spectrometry. 3+ The ion concentrations are shown in Table 2.
[0081] Table 2:
[0082]
[0083] (3) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add 250ml of 50mg / L Sb at pH 6 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Sb in the solution was determined by atomic absorption spectrometry. 3+ Ion concentration, the results are shown in Table 3 below.
[0084] Table 3:
[0085]
[0086] (4) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: pH = 2, 250ml, 50mg / L Sb 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Sb in the solution was determined by atomic absorption spectrometry. 3+ Ion concentration, the results are shown in Table 4 below.
[0087] Table 4:
[0088]
[0089] (5) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: pH = 3, 250ml, 50mg / L Sb 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Sb in the solution was determined by atomic absorption spectrometry. 3+ Ion concentration, the results are shown in Table 5 below.
[0090] Table 5:
[0091]
[0092] (6) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: pH = 5, 250 ml, 50 mg / L Sb 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Sb in the solution was determined by atomic absorption spectrometry. 3+ Ion concentration, the results are shown in Table 6 below.
[0093] Table 6:
[0094]
[0095] Comparison of different adsorbents on Sb 3+ The adsorption effect of ions is shown in Table 7.
[0096] Table 7:
[0097]
[0098] As shown in Tables 1 to 7 above, the adsorbent prepared by the present invention has a high adsorption capacity at pH = 5 and 50 mg / L Sb 3+ In ionic solutions, compared with other pH and concentrations of Sb 3+ , the adsorption equilibrium was reached in 120 min, and the maximum adsorption capacity was 36.75 mg / g.
[0099] Effect verification 2:
[0100] (1) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: pH 4.5, 250 ml, 12.5 mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 8 below.
[0101] Table 8:
[0102]
[0103] (2) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add pH 4.5, 250ml, 25mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 9 below.
[0104] Table 9:
[0105]
[0106] (3) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add 250ml of 50mg / L Pb at pH 4.5 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 10 below.
[0107] Table 10:
[0108]
[0109] (4) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add pH 4.5, 250ml, 100mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 11 below.
[0110] Table 11:
[0111]
[0112] (5) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add pH 3.5, 250ml, 50mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 12 below.
[0113] Table 12:
[0114]
[0115] (6) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add pH 5.5, 250ml, 50mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 13 below.
[0116] Table 13:
[0117]
[0118] (7) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add pH 6.5, 250ml, 50mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 14 below.
[0119] Table 14:
[0120]
[0121] (8) 0.6 g / L SA-EMR 2∶1Adsorbent dosage: Add pH 5.5, 250ml, 100mg / L Pb 2+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 60-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion concentration, the results are shown in Table 15 below.
[0122] Table 15:
[0123]
[0124] As shown in Tables 8 to 15 above, the adsorbent prepared by the present invention has a good adsorption performance at pH = 4.5 and 100 mg / L Pb 2 In ion solution, compared with other concentrations of Pb 2 , the adsorption equilibrium was reached in 100 min, and the maximum adsorption capacity was 157.92 mg / g.
[0125] Effect verification 3:
[0126] (1) 0.6 g / L SA-EMR 2∶1 Adsorbent dosage: Add 250ml of 50mg / L Pb at pH 4.5 2+ Ion, 50mg / LSb 3+ The ion solution was placed on a 120 rpm shaker, and samples were taken at 20-min intervals. The remaining Pb in the solution was determined by atomic absorption spectrometry. 2+ Ion, Sb 3+ Ion concentration, the results are shown in Tables 16 and 17 below.
[0127] Table 16:
[0128]
[0129] Table 17:
[0130]
[0131] It can be seen from Tables 16 and 17 that when two heavy metal ions of lead and antimony exist at the same time, the adsorbent preferentially adsorbs trivalent antimony ions, and the maximum adsorption capacity is not much reduced compared to a single antimony ion solution. On the contrary, compared to a single lead ion solution, when two heavy metal ions of lead and antimony exist at the same time, the maximum adsorption capacity of the adsorbent for lead ions is significantly reduced. It is preferred to use the adsorbent of the present invention for selectively adsorbing antimony ions in antimony mine wastewater containing both heavy metal ions of lead and antimony. It is preferred to first adjust the pH of the acidic antimony mine wastewater to 4-6, and the addition amount of the acidic antimony mine wastewater heavy metal adsorbent is 0.6-1g per liter of acidic antimony mine wastewater.
[0132] In summary, the present invention uses Class II general industrial solid waste electrolytic manganese slag as raw materials to compound sodium alginate and polyacrylamide, and prepares a high-efficiency selective adsorption gel through a simple hydrothermal method. The gel adsorbent not only overcomes the difficulties of general activated electrolytic manganese slag adsorbent powder being difficult to separate and recycle, but also overcomes the problems of poor mechanical properties of sodium alginate-based adsorbents. In addition, the present invention has good adsorption performance for single lead and antimony heavy metal ions, and when two heavy metals exist at the same time, the composite adsorbent has good selective adsorption for trivalent antimony ions. Therefore, the present invention not only provides a new path for the high-value resource utilization of electrolytic manganese slag, but also provides a new material for the adsorption and removal of lead and antimony heavy metal ions in acidic antimony mine wastewater.
[0133] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. An application of a heavy metal adsorbent for acidic antimony mine wastewater, characterized in that: The preparation method of the acid antimony mine wastewater heavy metal adsorbent comprises the following steps: S1, adding sodium alginate into the aqueous solution, stirring at a constant temperature, to obtain a paste-like uniform sodium alginate aqueous solution; S2, adding electrolytic manganese slag to the sodium alginate aqueous solution, stirring and ultrasonically treating to form a uniform first solution; S3, preparing an ammonium persulfate (APS) initiator solution, adding it to the first solution to obtain a second solution; S4, preparing a sodium hydroxide solution and an acrylic acid (AA) solution, and adding them into the second solution to obtain a third solution; S5, preparing an acrylamide (AM) solution, and adding the solution to the third solution to obtain a fourth solution; S6, preparing NN methylenebisacrylamide (MBA) solution, and adding it into the fourth solution to obtain a fifth solution; Under the hydroponic condition of 60-65° C., the fifth solution is subjected to a cross-linking reaction. After the cross-linking reaction is completed, the adsorption gel is washed with deionized water until it is neutral, and dried to obtain a sodium alginate-electrolytic manganese slag-polyacrylamide adsorbent; The mass ratio of sodium alginate to electrolytic manganese slag is 2:1; It is used for selectively adsorbing antimony ions in antimony mine wastewater containing both lead and antimony heavy metal ions; the antimony ions in the antimony mine wastewater are trivalent antimony ions.
2. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: In step S6, the cross-linking reaction time is 8 to 12 hours.
3. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: In step S1, the sodium alginate is analytically pure; the mass-to-liquid ratio of the sodium alginate aqueous solution is 5g:35-45ml; the stirring temperature is 80-90°C, and the stirring time is 30-40min.
4. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: In the step S2, the stirring ultrasonic treatment includes stirring for 15 to 20 minutes at a rotation speed of 30 r / min, and ultrasonicating for 15 to 30 minutes at an ultrasonic power of 200 W; the pretreatment of the electrolytic manganese slag includes: calcining at 400-600° C., crushing and then passing through a 100-mesh sieve to obtain the undersize.
5. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: The mass ratio of sodium alginate to ammonium persulfate (APS) initiator is 5:0.1-0.15; the mass ratio of sodium alginate to sodium hydroxide is 5:1-1.5; the mass volume ratio of sodium alginate to acrylic acid (AA) is 5g:3-5ml; the mass ratio of sodium alginate to acrylamide (AM) is 5:0.8-1.2; the mass ratio of sodium alginate to NN methylenebispropylene (MBA) is 5:0.3-0.
4.
6. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: In the step S3, the temperature when the first solution is added is 75-80°C, and the reaction takes 3-5 minutes after the first solution is added; in the step S4, the temperature when the second solution is added is 75-80°C, and the reaction takes 3-5 minutes after the second solution is added; in the step S5, the temperature when the third solution is added is 75-80°C, and the reaction takes 3-5 minutes after the third solution is added.
7. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: In step S6, the drying temperature is 60-80°C.
8. The use of the heavy metal adsorbent for acidic antimony mine wastewater according to claim 1, characterized in that: First, the pH value of the acidic antimony mine wastewater is adjusted to 4-6, and the amount of the heavy metal adsorbent for acidic antimony mine wastewater added to each liter of the acidic antimony mine wastewater is 0.6-1 g.